Aquinói Szent Tamás a helyes államról és kormányzásról - Frivaldszky, János (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
In this paper we discuss St. Thomas Aquinas’ theory of the state and political government. We seek to answer why he believed that the best form of government is kingship. We will look at how to avoid the danger of the best form of government being distorted into its opposite, the worst form of government, tyranny. The criteria for this will be examined, and then we will analyse the second best form of government that can be implemented, a mixed government of limited monarchy. St. Thomas, although he lived in the age of constitutional charters and was familiar with them, chose the government of virtuous persons for the common good, rather than the constitutional system of charters based on ’institutionalised distrust’.